Human connection with nature improves wellbeing and pro-environmental behavior: A literature review - Devi Mariya Sulfa; Hadi Suwono; H. Husamah (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Given the world's continuous environmental concerns, there is a need for increased participation in nature protection. The ecological crisis of the last decade on Earth has become one of the causes of the rupture of society's relationship with nature. Such relationships can predict diverse attitudes, concerns, intentions, and pro-environmental behavior (PEB). A systematic literature review (SLR) aims to compare, study, and analyze journal articles that relate to issues related to nature as a major factor in pro-environmental behavior. The results of selecting articles indexed by SCOPUS found as many as 1716 publications. The 50 open-access publications of articles were chosen based on specific criteria and further examined to identify eight final articles that align with the Inclusion of Nature in Self (INS) scale. Pro-environmental behavior strengthens human relationships with nature and encourages a sense of ownership and involvement with the environment. Pro-environmental behavior refers to behaviors that are beneficial to the environment, such as supporting conservation policies, recycling, and participating in nature. Research using INS scale, which focuses on connections with nature, still has significant potential and should persist in making contributions to science and humanity.